RURAL YOUNG: UNIVERSITY PERMANENCE AT UFF CAMPOS - Ferreira Maciel, Thaynara; Corsino Pérez, Beatriz (LINKSCIENCEPLACE, 2026)
The municipality of Campos dos Goytacazes is a reference for higher education in the northern region of the state of Rio de Janeiro, with several public and private universities. This research aims to analyze the permanence of young people from rural areas of Campos dos Goytacazes at the Fluminense Federal University, given that the expansion of the university profile as a result of affirmative action policies has also changed the challenges faced in terms of student permanence, which can be understood on two levels: material and symbolic. To this end, bibliographical research was carried out on university permanence, youth and territory, together with interviews with six rural young people from different courses at UFF Campos and with the student assistance team. The results show that many young people receive aid and grants to help them stay at university, but they also highlight student assistance projects and participation in research and extension groups that contribute to their sense of belonging to the university and to their symbolic permanence. However, there is still a need to expand student assistance policies to cover more students.